The Vlachs in Byzantium – until the beginning of the 11th century - Dudek, Jarosław (Balcanica Posnaniensia. Acta et studia, 2021)
Byzantine sources up to the 10th century do not mention the Vlachs, but they contain information about the groups of Romans inhabiting the Avar and Bulgar states in the period between 7th and 10th century. After the conquests of Emperor Basil II, the Balkans returned under the Byzantine rule. However, the Vlachs did not obtain the status of the Romans (Rhomaioi) but were treated as semi-barbarian subjects (Bulgarians, Serbs).